A Hybrid Approach for Performing Accurate prediction of Green Products using Recommender System - Kaur, Jatinder; Bedi, Rajeev Kumar; Gupta, S.K (International Journal of Computer Sciences and Engineering, 2025)
Today many distinct products exists along with the configuration. Technology is advancing as well, proposed system deals with recommender system based on KNN clustering techniques. KNN along with filtering mechanism is introduced as a base mechanism to predict most likely products to be promoted through the recommender system. Simulation results indicates that the C-KNN (Content based K nearest neighbour technique is better than individual approaches of KNN and content based filtering.